2006
DOI: 10.1111/j.1530-0277.2006.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Drinking Among Women of Child‐Bearing Age

Abstract: Drinking and heavier drinking remain at high levels among women of child-bearing age. Prevention efforts must be comprehensive and should target pregnant women who are drinking and those who could become pregnant and are drinking at high-risk levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 36 publications
10
105
4
Order By: Relevance
“…In line with previous research, our research identified age as influential in terms of mothers' alcohol use [1][2][3][4][5][6][7][8][9][10]. Mothers linked youth with heavy alcohol consumption and frequent small quantities of alcohol use were considered indicative of older age groups.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In line with previous research, our research identified age as influential in terms of mothers' alcohol use [1][2][3][4][5][6][7][8][9][10]. Mothers linked youth with heavy alcohol consumption and frequent small quantities of alcohol use were considered indicative of older age groups.…”
Section: Discussionsupporting
confidence: 64%
“…There is evidence that problematic alcohol use (DSM-III-R, CAGE criteria) and binge drinking (>4 drinks, >60 g alcohol per occasion) among women is negatively associated with age [1][2][3][4][5][6][7][8][9][10]. Social gradients in alcohol use have also been identified amongst women [11] and young adults [12].…”
Section: Introductionmentioning
confidence: 99%
“…First, binge drinking is more clinically relevant than continuous alcohol exposure (Caetano et al, 2006). For reference, the amount of alcohol needed to bring human alcohol blood level to 200 mg/dL -as in our sheep -is 7 ounces of hard liquor or 7 beers consumed over a 90 minute period.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of alcohol consumption among women of child-bearing age remains essentially unchanged despite considerable efforts to educate women about the harmful consequences of alcohol consumption during pregnancy (Caetano et al, 2006;CDC, 2004;Institute of Medicine, 1996;Maternal and Child Health (MCH) Data Report, 2003;NIAAA, 2000) requiring the need to consider other approaches to reduce the negative impact of prenatal alcohol exposure (Cudd, 2005). Numerous hypotheses have been proposed to account for the teratogenic effects of alcohol of which alcohol induced alterations in hypothalamic-pituitaryadrenal (HPA) axis, and hypothalamus-pituitary-thyroid (HPT) axis function are popular (For review, see Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we characterized the T 3 , T 4 and free T 4 responses in pregnant sheep to alcohol exposure, but extending the duration of alcohol exposure to all three trimesterequivalents of gestation. We employed a "binge" alcohol exposure paradigm, a drinking pattern common in women who use alcohol during pregnancy (Caetano et al, 2006;Cudd et al, 2001;Ebrahim et al, 1999;Gladstone et al, 1996;Maier and West, 2001) to characterize the maternal thyroid hormones, ACTH and cortisol responses to alcohol over the entire period of gestation.…”
Section: Introductionmentioning
confidence: 99%